S01.1 Extramedullary hematopoiesis and immune training contribute to tissue inflammation in sle by providing inflammatory license to bone marrow-derived hematopoietic stem and progenitor cells (HSPCS). (27th September 2022) - Zervopoulou, E; Doumas, S; Banos, A; Gakiopoulou, H; Mitroulis, I; Boumpas, DT; Grigoriou, M
Abstract : Purpose: We have previously shown dysregulation of hematopoiesis in the bone marrow (BM) in SLE, with skewing towards the myeloid lineage and evidence for extramedullary hematopoiesis (EMH). EMH results in the generation of effector cells in the periphery to meet the increased demands and has been linked to peripheral tissue injury by proving an inflammatory license to BM-derived cells. We sought to further explore their contribution to disease pathology. Materials and Methods: Meta-analysis of peripheral blood (PB-) and BM-derived CD34+ cells transcriptomic data and of BM-derived HSPCs from pre-diseased (F1-P) and lupus (F1-L) NZBW/F1 mice was conducted. 1, 2 Immune profiling performed in BM, spleen and kidneys of NZBW/F1 mice and their age-matched controls (B6-Y and B6-O respectively). BM- and spleen-derived HSPCs were seeded for CFU-assay. For the trained immunity experiments, F1-P mice were injected ip with β-glucan/PBS every 15 days, until the emergence of nephritis. Results: In SLE patients, BM- and PB CD34+ transcriptome exhibited signature profiles consistent with activation and migration, with PB CD34+ appearing positively enriched in 'Migration'' and 'BM exit' pathways. Human results were mirrored in the murine transcriptomic data. CXCR4, a key factor for HSPC retention to the BM, was decreased in HSPCs and myeloid progenitors (MPs) from lupus mice. In the spleen of F1-L mice both HSPCs and GMPs (granulocyte-monocyte progenitors) were expanded and the latter was confirmed by CFU assay. HSPC and MP frequencies presented increase in the kidneys of F1-P. Administration of the innate immunity primer β-glucan exaggerated the histology of glomerulonephritis with increased activity indices of LN. GMP frequency increased in the BM with concomitant increase of LT-HSC frequency and splenic EMH. Conclusions: In SLE, HSPCs activation and exit from the BM is orchestrated by CXCR4 leading to engraftment and formation of differentiation clusters into the spleen and the kidneys. Consistent with the granulopoiesis profile observed in the BM, peripheral HSPC sustain their myeloid skewing. Reprogramming of innate effector cells exaggerate LN and augment EMH providing 'trained' immune cells that sustain and amplify the inflammatory response. References: Grigoriou M, Banos A, Filia A, et al . Transcriptome reprogramming and myeloid skewing in haematopoietic stem and progenitor cells in systemic lupus erythematosus. Ann Rheum Dis 2020;79 :242–253. Kokkinopoulos I, Banos A, Grigoriou M, et al . Patrolling human SLE haematopoietic progenitors demonstrate enhanced extramedullary colonisation; implications for peripheral tissue injury. Sci Rep 2021;11 :15759.